Rewriting Maimonides: early commentaries on the Guide of the Perplexed - De Souza, Igor H. (Jewish thought, philosophy, and religion, 2018)
Commentaries on the Guide of the Perplexed occupy a central but neglected place in the history of Jewish thought. In the first study on the subject, Igor De Souza examines this dynamic tradition in its most creative period. Rather than mere interpretation, De Souza reads commentaries as texts in their own right. At the same time, he illustrates how texts are reimagined through commentary, and repurposed for new generations of readers